The Renal Community Photo Initiative: A Program Report in Ontario, Canada. (May 2022) - Skinner, Ruth; House, Cindy; House, Andrew A.; McIntyre, Chris; Hayter, Elaine; Ireland, Pamela; McGregor, Jared; Tillmann, Ann
Purpose of Program: We initiated the Renal Community Photo Initiative to better understand why some hemodialysis users express significant capacities for resilience and hope, demonstrating outward-looking perspectives and enjoying a rich quality of life. Sources of Information: "Photovoice" is a participatory research methodology that encourages individuals to develop positive self-perceptions with photography. Photovoice empowers participants as informants within their communities. Visual arts researchers surveyed existing Photovoice studies to identify gaps in knowledge to be addressed in this study, including challenges related to fostering participant agency and social action. Images and logs were collected and reviewed during organized, participant-led substudy groups. These meetings provided researchers with core study values and direction as to how the images and additional information should be used to raise awareness about living with chronic kidney disease. Methods: To address the complexity of the human condition, the Renal Community Photo Initiative offered participants an array of diverse and accessible image-making techniques. No narrative directives for image-making were provided. This qualitative, interdisciplinary, participant-centric study invited adult chronic hemodialysis patients in 4 dialysis units in London and Stratford, Ontario, to participate. The research team designed a selection of different, accessible photo technologies for participant use. Eligible participants were invited to select photographic technologies and given the additional option to write accompanying logs. Researchers organized substudy meetings for participant-led focus groups to discuss core study values and personal encounters with images and image-making. Participants directed how their generated images should be shared with the public and researchers. Key Findings: A total of 40 participants have been recruited to date, producing more than 1600 images and an archive of handwritten logs. Three participant-led focus groups have established priorities for image sharing and a core set of values for subsequent study phases. A series of public presentations of participant images took place. The research team will pursue further public presentation opportunities and the development of a suitable research database. Limitations: Organizing and categorizing images for access in an interdisciplinary research database remains a challenge. Current health and safety protocols related to COVID-19 require the study to pause recruitment and substudy meetings and reassess immediate outputs for visuals. Implications: A qualitative study of this scope offers a new model for participant agency and collaboration. It requires the onboarding of interdisciplinary researchers to effectively engage with its significant image and log archive. Participants should remain involved in directing future steps for disseminating their images. Following substudy directives, researchers are developing visuals for health care and public settings, and determining opportunities for participants to share their experience in both clinic- and public-based settings.